Multi-input multi-output converter with battery charger for low power applications - Pradeep Kumar, S; Krishnakumar, R; N.Ganesh, E (International Journal of Engineering and Technology, 2018)
For low power applications an integrated type multi- input multi- output converter with battery charger was presented in this paper. Power can be delivered from different sources with low power switching device using the proposed topology. The circuit model is designed to reduce the switching losses and to improve the converter overall efficiency by charging the battery using transformer leakage inductance. The input power distribution includes two input sources are operated by this converter model. This paper proposed a 20 â€“W prototype to test the converter performance and the experimental results are shown.Â Â